There will be Predictive Association between Coronavirus Anxiety and Psychological Well-being among Emerging Adults during Pandemic - Aqsa Fayyaz; Komal Hayat; Muhammad Bilal Arif (Research Journal of Psychology, 2025)
The COVID-19 pandemic has severely affected mental health worldwide, particularly among emerging adults navigating the transitional phase between adolescence and adulthood. This population is especially vulnerable to psychological stressors due to heightened uncertainty, disrupted routines, and limited coping mechanisms. The present study aimed to determine the predictive association between Coronavirus Anxiety and Psychological Well-being among emerging adults in Karachi, Pakistan. Using a quantitative correlational research design, data were collected from 300 participants aged 18 to 25 through purposive non-probability sampling. Participants completed the Coronavirus Anxiety Scale (CAS) and Ryff’s Psychological Well-being Scale (PWB) via an online Google Forms survey. Descriptive statistics and Pearson correlation analysis were conducted using SPSS version 21. Findings revealed a significant negative correlation between coronavirus anxiety and psychological well-being (r = –.22, p < .01), suggesting that increased anxiety levels are associated with diminished psychological well-being in emerging adults. The internal consistency of both scales was acceptable (α = .698 for CAS, α = .674 for PWB). The results support existing literature indicating that pandemic-induced anxiety is a risk factor for poor mental health outcomes. The study contributes to a growing body of research on the long-term psychological consequences of the pandemic and highlights the importance of developing targeted mental health interventions. These should focus on enhancing resilience, fostering emotional regulation, and increasing access to mental health services—especially in low- and middle-income countries where resources are often limited. Future research may explore the potential mediating role of variables such as gratitude, coping strategies, or social support in mitigating anxiety’s impact on well-being.